2012
DOI: 10.1007/s11557-012-0839-5
|View full text |Cite
|
Sign up to set email alerts
|

Phellinus castanopsidis sp. nov. (Hymenochaetaceae) from southern China, with preliminary phylogeny based on rDNA sequences

Abstract: Phellinus castanopsidis sp. nov. is described and illustrated from southern China. This species is characterized by resupinate, annual basidiomata, a dimitic hyphal system, hooked hymenial setae, and ovoid to broadly ellipsoid basidiospores that are colorless, thick-walled, weakly dextrinoid, and moderately cyanophilous. Most of these morphological features are shared by Fomitiporia ellipsoidea, P. gabonensis, and P. caribaeo-quercicolus, although in the two latter species, the basidiospores are not dextrinoid… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2012
2012
2018
2018

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 24 publications
(5 citation statements)
references
References 30 publications
0
5
0
Order By: Relevance
“…Although steroids are rather common in the Basidiomycota, they have not been reported yet from the genus Fomitiporia . Studies on Fomitiporia ellipsoidea metabolites indicated that this fungus produced a large amount of common ergosterol and its derivatives but this species has since been moved to the genus Phellinus (currently valid name: Phellinus ellipsoidea ) [ 11 , 12 ]. The close relationship between these two genera has seen the transfer of several other species previously assigned to the genus Phellinus to the genus Fomitiporia , examples being species like F. erecta , F. hartigii , F. robusta , F. punctata , F. hippophaeicola and F. pseudopunctata [ 13 ].…”
Section: Resultsmentioning
confidence: 99%
“…Although steroids are rather common in the Basidiomycota, they have not been reported yet from the genus Fomitiporia . Studies on Fomitiporia ellipsoidea metabolites indicated that this fungus produced a large amount of common ergosterol and its derivatives but this species has since been moved to the genus Phellinus (currently valid name: Phellinus ellipsoidea ) [ 11 , 12 ]. The close relationship between these two genera has seen the transfer of several other species previously assigned to the genus Phellinus to the genus Fomitiporia , examples being species like F. erecta , F. hartigii , F. robusta , F. punctata , F. hippophaeicola and F. pseudopunctata [ 13 ].…”
Section: Resultsmentioning
confidence: 99%
“…[70], Lenzitopsis Malençon & Bertault [71], Lignosus Lloyd ex Torrend [72], Perenniporia Murrill [73], Phellinus Quél. [74], Phylloporia Murrill [75], Pseudochaete T. Wagner & M. Fisch. [76], Theleporus Fr.…”
Section: Taxonomy and Phylogenymentioning
confidence: 99%
“…Recently, molecular data along with morphology were used to certify the taxonomy and phylogeny of wood-inhabiting fungi in China (Cui et al 2008, 2011b, Cui 2013, Cui & Decock 2013, Li & Cui 2013, Tian et al 2013, Yuan 2013, Zhao & Cui 2013, Zhao et al 2013). During investigations of wood-inhabiting fungi in China, nearly 200 specimens were preliminarily identified as Datronia spp., but their taxonomic affinities and phylogenetic relationships remain uncertain.…”
Section: Introductionmentioning
confidence: 99%
“…In the last two decades, extensive taxonomic studies of wood-inhabiting fungi in China have been carried out, and many new species were described based on morphological characters ( Dai 1995 , Dai & Niemelä 1997 , Langer & Dai 1998 , Dai et al 2002 , 2003 , 2004 , 2009 , 2010 , 2011 , Cui & Dai 2006 , Cui et al 2011a , Dai 2010 , Li & Cui 2010 , He & Li 2011 ). Recently, molecular data along with morphology were used to certify the taxonomy and phylogeny of wood-inhabiting fungi in China ( Cui et al 2008 , 2011b , Cui 2013 , Cui & Decock 2013 , Li & Cui 2013 , Tian et al 2013 , Yuan 2013 , Zhao & Cui 2013 , Zhao et al 2013 ). During investigations of wood-inhabiting fungi in China, nearly 200 specimens were preliminarily identified as Datronia spp., but their taxonomic affinities and phylogenetic relationships remain uncertain.…”
Section: Introductionmentioning
confidence: 99%